Novel Oral Anticoagulant Use Among Patients with Atrial Fibrillation Hospitalized with Ischemic Stroke or Transient Ischemic Attack - Patel, Priyesh A. (Circ Cardiovasc Qual Outcomes, 2015)
BACKGROUND: Novel oral anticoagulants (NOACs) have been shown to be at least as good as warfarin for preventing stroke or transient ischemic attack (TIA) in patients with atrial fibrillation (AF), yet diffusion of these therapies and patterns of use among AF patients with ischemic stroke and TIA have not been well characterized. METHODS AND RESULTS: Using data from Get With The Guidelines(®)–Stroke, we identified a cohort of 61,655 AF patients with ischemic stroke or TIA hospitalized between 10/2010–09/2012 and discharged on warfarin or NOAC (either dabigatran or rivaroxaban). Multivariable logistic regression was used to identify factors associated with NOAC versus warfarin therapy. In our study population, warfarin was prescribed to 88.9%, dabigatran to 9.6%, and rivaroxaban to 1.5%. NOAC use increased from 0.04% to a 16–17% plateau during the study period, though anticoagulation rates among eligible patients did not change appreciably (93.7% vs. 94.1% from first quarter 2011 to second quarter 2012), suggesting a trend of switching from warfarin to NOACs rather than increased rates of anticoagulation among eligible patients. Several bleeding risk factors and CHA(2)DS(2)-VASc scores were lower among those discharged on NOAC versus warfarin therapy (47.9% vs. 40.9% with CHA(2)DS(2)-VASc ≤5, p<0.001 for difference in CHA(2)DS(2)-VASc). CONCLUSIONS: NOACs have had modest but growing uptake over time among AF patients hospitalized with stroke or TIA and are prescribed to patients with lower stroke risk compared to warfarin.